Poetology: Problems of Constructing a Thesaurus and Verse Text Specification - Vladimir N. Boykov; Maria S. Karyaeva (Моделирование и анализ информационных систем, 2017)
It is a brief version of the report made by the authors at the seminar “Modeling and Analysis of Information Systems”, Yaroslavl, May 17, 2017. The interrelation of problems of computeraided constructing the thesaurus and specification of verse texts in poetology is considered.